Distributed Generation Allocation to Improve Steady State Voltage Stability of Distribution Networks Using Imperialist Competitive Algorithm - Navid Ghaffarzadeh; Masoud Akbari; Amir Khanjanzadeh (Institute of Advanced Engineering and Science, 2013)
In this paper, a new method is proposed to optimal distributed generation allocation for stability enhancement in radial distribution networks. Voltage stability is related with stable load and acceptable voltage in all buses of system. According to the time spectrum of the incident of the phenomena the instability is divided into steady state and transient voltage instability. The analysis is accomplished using a steady state voltage stability index which can be evaluated at each node of the distribution system. Different optimal locations and capacities are used to check this effect. The location of DG is more important in comparison with the capacities and has the main effect on the network voltage stability. Effects of capacity and location on increasing steady state voltage stability in radial distribution networks are evaluated through Imperialist Competitive Algorithm (ICA) and at the end the results are compared to particle swarm optimization and genetic algorithm on the terms of speed, accuracy and convergence.